2006
DOI: 10.1111/j.1745-7262.2006.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic risks of intracytoplasmic sperm injection method

Abstract: Pregnancies achieved by assisted reproduction technologies, particularly by intracytoplasmic sperm injection (ICSI) procedures, are susceptible to genetic risks inherent to the male population treated with ICSI and additional risks inherent to this innovative procedure. The documented, as well as the theoretical, risks are discussed in the present review study. These risks mainly represent that consequences of the genetic abnormalities underlying male subfertility (or infertility) and might become stimulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 223 publications
1
58
0
13
Order By: Relevance
“…Since the analyzed infertile patients showed severe morphological and meiotic spermatogenetic impair ment, and inter individual variations cannot be pre dicted [10], a detailed ultrastructural and chromosomal analysis of spermatozoa from every reciprocal trans location carrier is advisable before undertaking ICSI cycles, and it is important to discuss with couple the option of Preimplantation Genetic Diagnosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Since the analyzed infertile patients showed severe morphological and meiotic spermatogenetic impair ment, and inter individual variations cannot be pre dicted [10], a detailed ultrastructural and chromosomal analysis of spermatozoa from every reciprocal trans location carrier is advisable before undertaking ICSI cycles, and it is important to discuss with couple the option of Preimplantation Genetic Diagnosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence rate of robertsonian translocation (RT) is 0.9 in infertile males, this figure is 9 times higher than in the general population [27,28]. Reciprocal translocations are observed in 0.9 of 1000 newborns and involve exchange of two unrelated chromosomal segments [29]. They have been found in approximately 1 % of infertile men and commonly occur in azoospermic men compared to oligozoospermic males [16,30].…”
Section: Chromosomal Translocationsmentioning
confidence: 99%
“…In addition, AZFc deletions are associated with testicular histologies varying from hypo-spermatogenesis (HP) to MA or SCOS [59]. Recently, studies have demonstrated that although only the AZFa and AZFb regions are required to initiate spermatogenesis, without the AZFc region, spermatogenesis will not be completely normal [29].…”
Section: The Azfb (P5/proximal-p1) Regionmentioning
confidence: 99%
“…Assisted reproduction technologies in general and intracytoplasmic sperm injection in particular, currently are a treatment option for patients with reduced sperm counts. However, intracytoplasmic sperm injection increases the chances of bypassing chromosomal abnormalities to the offspring, thus increasing the probability of developing malformations of genetic origin [12]. Therefore, cytogenetic analysis of patients with azoospermia and oligozoospermia is mandatory before infertility treatment with assisted reproduction technologies.…”
Section: Introductionmentioning
confidence: 99%